Digital Transformation in Human Resource Management: Integrating Artificial Intelligence, Talent Development, and Organizational Sustainability in the Digital Age - Basri Modding; Azis Rachman; Titin Dunggio (Westscience Press, 2026)
Digital transformation in human resource management has become an important strategy for organizations to improve work effectiveness, competitiveness, and organizational sustainability in the digital era. This study aims to analyze the influence of Artificial Intelligence Integration, Talent Development, and Organizational Sustainability on the Digital Transformation of Human Resource Management. The study uses a quantitative approach with a survey method. The study population is employees and management staff in several organizations and companies in Gorontalo Province that have implemented digital systems in HR management. The sampling technique used purposive sampling with a sample size of 120 respondents. Data collection was carried out by distributing questionnaires using a Likert scale of 1–5. The data analysis technique used multiple linear regression analysis with the help of SPSS software. The results of the study indicate that Artificial Intelligence Integration, Talent Development, and Organizational Sustainability have a positive and significant effect on the Digital Transformation of Human Resource Management. The Artificial Intelligence Integration variable is the most dominant variable in influencing the digital transformation of HR. Furthermore, the coefficient of determination showed an R² value of 70.9%, indicating that the three independent variables were able to explain 70.9% of the influence on Digital Transformation of HR Management, while the remainder was influenced by other variables outside the study. This study implies that the success of an organization's digital transformation depends not only on technology, but also on the development of digital talent competencies and the organization's ability to build a sustainable and adaptive work system to technological change.